Controle do escoamento superficial e das perdas de solo em sistema plantio direto na escala de lavoura - Deuschle, Dinis (2016)
The evidence of the formation of surface flow and associated processes such as erosion, transfer of solutes, organic matter and nutrients, are the consequences of soil management not contributing to the maintenance of soil functions, especially those associated to the regulation of hydrological flows. This situation leads to soil degradation, degradation of water resources and waste inputs. Considering the principles of conservation agriculture, numerous practices of soil, plant and field management are likely to be used in order to solve problems. Given this, the objective of this work was to evaluate the influence of the addition phytomass and scarification in the control of surface flow and soil losses in grain production areas using direct planting at slope scale during significant rain events. The monitoring was conducted in six rectilinear macro plots, with dimensions of 70x80m and average steepness of 9%, in a Red Latosol. The study was carried out between 2014 and 2016 in the city of Júlio de Castilho, RS, and observed the responses in surface flow and suspended sediment concentration during significant rain events. There were different systems of soil management (three with scarification and three without) and coverage depending on crop rotation (two with low addition and 4 with medium addition of phytomass) in each of the macro plots. Agricultural practices in the plots followed technical recommendations for grain production (soy/wheat/oats) in southern Brazil. During 12 months, nine significant rain events were monitored. The monitoring data were evaluated to characterize the magnitude of hydrological and erosive responses between treatments over the course of time. Not surprisingly, results show that both practices reduce surface flow and soil losses. However, the addition of biomass presented higher efficiency than scarification. Results also show that for extreme precipitation events the two practices are unable to control all of the surface flow. Moreover, the monitoring of events over time revealed the behavior of the flow and sediment concentration, thus making it possible to understand the mechanism hydrologic response of the different rain events to different handling conditions throughout the year and between events. Keywords: Soil Conservation. No Til